2004
DOI: 10.1016/j.crci.2003.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Composition chimique et activités biologiques de l'huile essentielle de Lantana camara Linn.

Abstract: La composition chimique de l'huile essentielle extraite des feuilles fraîches de Lantana camara Linn. récoltées sur le campus d'Abomey-Calavi (Bénin) a été étudiée par chromatographie en phase gazeuse couplée avec la spectrométrie de masse (CG et CG/SM). Quarante et un constituants, représentant 94,76 % de l'huile essentielle de Lantana camara, ont été identifiés. Les composés majoritaires sont : b-caryophyllène 18,5 % ; sabinène 13,1 % ; a-humulène 10 % ; 1,8-cinéole 9 % ; d-guaiene 5,0 %. Cette huile, testée… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
12
1
Order By: Relevance
“…Essential oil was obtained by hydrodistillation with a yield of 0.6% and was yellow in color. This yield is higher than that obtained by Alitonou et al, (2004) and Sonibare and Effiong (2008). This difference could be related to the zone of collection, the nature of the ground, the stage of development of the plant (Adjou and Soumanou, 2013) and the method used for essential oil extraction (Ogunsina et al, 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…Essential oil was obtained by hydrodistillation with a yield of 0.6% and was yellow in color. This yield is higher than that obtained by Alitonou et al, (2004) and Sonibare and Effiong (2008). This difference could be related to the zone of collection, the nature of the ground, the stage of development of the plant (Adjou and Soumanou, 2013) and the method used for essential oil extraction (Ogunsina et al, 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…It should be noted that many sesquiterpenes identified in the essential oil extracted from leaves also occurred in the oil extracted from stems, independently of collection time. With concentration above 10%, the predominant compounds in the analysis described in the literature were: germacrene D, limonene, δ-curcumene, curcumene, davanone and 1,8-cineole (Ngassoum et al, 1999;Silva et al, 1999;Misra & Laatsch, 2000;Alitonou et al, 2004;Hernández et al, 2005;Sonibare & Effiong, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…In relation to chemical volatile constituents from genus Lantana, previously published studies showed a predominance of mono and sesquiterpenes Ngassoum et al, 1999;Silva et al, 1999;Misra & Laatsch, 2000;Alitonou et al, 2004;Hernández et al, 2005;Sonibare & Effiong, 2008). In this sense, we recently analyzed leaves of Lantana species by GC-MS collected in Ceará, Brazil, and it showed that essential oils from these species have in its composition mainly sesquiterpenes and sesquiterpenoids Sousa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent Inhibition was calculated using a formula: % Inhibition =100 -[(Abs sample −Abs blank ) × 100/ Abs control ] Where Abs sample is the absorbance obtained in the presence of USPE extract concentrations and Abs control is that obtained in the absence of extracts. The concentration necessary to inhibit 50% radical formation, inhibitory capacity IC 50 were obtained by extrapolating the graph obtained by plotting the % inhibition versus different concentrations of USPE extracts, determined in triplicate.…”
Section: Radical-scavenging Activity-dpph Assaymentioning
confidence: 99%